Utilization of Mangosteen Skin Into A Halal Drink and Thayyib As A Business Opportunity In The Form Of Health Coffee Powder - nuraini, nuraini; vinuzia, mala (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to educate the public so that they can use mangosteen peel waste that has been consumed, so that it is not turned into useless waste, but can be used as a selling point that is beneficial for health and to help the creative economy for residents and SMEs in the hamlet. Ireng Daye, Jatisela Village, Gunungsari District, West Lombok Regency. The method used in this study was direct observation, with a validation test of the efficacy of mangosteen peel coffee, the type of qualitative research, while the data sources used were primary and secondary data, namely finding and collecting various information and records, books, journals that related to the object of research. The problem faced is the local community's lack of awareness of the benefits of mangosteen peel so that the mangosteen peel waste is not responded to properly, due to the lack of human resources and knowledge of the benefits of mangosteen peel. The results showed that instant KBM powder contained alpha-mangostin levels of 0.59 mg/g, anthocyanins 1.13 mg/g, and phenolic levels of 8.49 mg/g per unit weight of dry sample. the conclusion of this study. In order to be used as a herbal medicinal product is mangosteen rind. The most popular benefit is to overcome heart disease, cancer and other degenerative diseases. In order to be useful as a business opportunity by various ways of packaging as original coffee powder drinks.